Enhancing an International Perspective in Public Health Teaching through Formalized University Partnerships - Brzoska, Patrick; Akgün, Seval; Antia, Bassey E.; Thankappan, K. R.; Nayar, Kesavan Rajasekharan; Razum, Oliver (Frontiers in Public Health, 2017)
Teaching in the field of public health needs to employ a global perspective to account for the fact that public health problems and solutions have global determinants and implications as well. International university partnerships can promote such a perspective through the strengthening of cooperation, exchange, and communication between academic institutions across national boundaries. As an example for such an academic network in the field of public health, we introduce the International Public Health Partnership—a collaboration between a university in Germany and universities in India, Turkey, and Nigeria. Formed in 2005, it facilitated the exchange of information, fostered discussion about the transferability of public health concepts, contributed to the structural development of the universities involved, and promoted an intercultural dialog through a combination of local and distance learning activities. Although well accepted by students and staff, different obstacles were encountered; these included limited external funding, scarce own financial, time and personnel resources, and diverging regulations and structures of degree programs at the partnership sites. In the present article, we share several lessons that we learned during our joint collaboration and provide recommendations for other universities that are involved in partnerships with institutions of higher education or are interested to initiate such collaborations.